Mild Physical Activity Does Not Improve Spatial Learning in a Virtual Environment - Ben-Zeev, Tavor; Weiss, Inbal; Ashri, Saar; Heled, Yuval; Ketko, Itay; Yanovich, Ran; Okun, Eitan (Frontiers in Behavioral Neuroscience, 2020)
It is well established that physical exercise in humans improves cognitive functions, such as executive functions, pattern separation, and working memory. It is yet unknown, however, whether spatial learning, long known to be affected by exercise in rodents, is also affected in humans. In order to address this question, we recruited 20 healthy young male adults (18-30 years old) divided into exercise and control groups (n=10 in each group). The exercise group performed 3 sessions per week of mild-intensity aerobic exercise for 12 weeks, while the control group was instructed not to engage in any physical activity. Both groups performed maximal oxygen uptake (VO2max) tests to assess their cardiovascular fitness at baseline and every 4 weeks through the 12 weeks of the training program. The effects of mild aerobic exercise were tested on performance in two different virtual reality (VR)-based spatial learning tasks: 1) virtual Morris water maze (VMWM) and 2) virtual Radial arm water maze (VRAWM). Subjects were tested in both tasks at baseline prior to the training program and at the end of 12 weeks training program. While the mild-intensity aerobic exercise did not affect subjects’ VO2max parameters, mean time to anaerobic threshold increased for the exercise group compared with control. No effect was observed, however, on performance in the VMWM or VRAWM between the two groups. Based on these results, we suggest that mild-intensity aerobic exercise does not improve spatial learning in young, healthy adults.